2005
DOI: 10.1671/0272-4634(2005)025[0950:tdoifs]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The difficulties of identifying flying squirrels (Sciuridae: Pteromyini) in the fossil record

Abstract: Two problems are examined in this paper: (1) the identification of flying squirrels in the fossil record by means of their teeth; and (2) the identification of features of the limbs that indicate that the animals were gliders. Dental features vary widely among flying squirrels and among other squirrels, and a thorough survey demonstrates that most features that have been used to distinguish fossil flying squirrels are also found in some tree squirrels. A review of the descriptions of fossil flying squirrels re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 20 publications
3
44
0
Order By: Relevance
“…Elongation of these bones without enlargement of many muscle attachments results in low scores for many of the muscle moment arms (shoulder moment index, humeral epicondylar index, olecranon length index, gluteal index, femoral epicondylar index, tibial spine index), with the consequence of reduced power and improved ranges of motion for these muscles. These findings are similar to a recent study of flying squirrels by Thorington et al (2005); they found relatively smaller deltopectoral crests, humeral epicondyles, and olecranon processes in gliding squirrels. More proximal insertion of the pectoralis and deltoid muscles in gliders would reduce power and increase mobility of the shoulder joint, whereas a smaller olecranon would allow full extension of the elbow.…”
Section: Glidingsupporting
confidence: 91%
“…Elongation of these bones without enlargement of many muscle attachments results in low scores for many of the muscle moment arms (shoulder moment index, humeral epicondylar index, olecranon length index, gluteal index, femoral epicondylar index, tibial spine index), with the consequence of reduced power and improved ranges of motion for these muscles. These findings are similar to a recent study of flying squirrels by Thorington et al (2005); they found relatively smaller deltopectoral crests, humeral epicondyles, and olecranon processes in gliding squirrels. More proximal insertion of the pectoralis and deltoid muscles in gliders would reduce power and increase mobility of the shoulder joint, whereas a smaller olecranon would allow full extension of the elbow.…”
Section: Glidingsupporting
confidence: 91%
“…Miosciurus covensis is smaller than any earlier tree squirrel known, suggesting a trend toward dwarfism in this lineage. This would represent the earliest dwarfing event in the fossil record of the Sciuridae; the extant members of this family include seven independently derived dwarf lineages (Thorington and Hoffmann 2005;Hautier et al 2009). If M. covensis is ancestral to M. ballovianus, which is approximately 15 -20% smaller (Tables 5-6), it would suggest this dwarfing trend continued through the end of the Oligocene.…”
Section: Miosciurus Covensis New Speciesmentioning
confidence: 99%
“…Emry and Korth (1996) raised doubts about identifying fossil flying squirrels purely from teeth. Pratt and Morgan (1989) and Thorington et al (2005) questioned the attribution of the genus to the Pteromyini based on characteristics of the dentition and astragalus. It is possible that the dental characters of Petauristodon and Sciurion may have arisen independently from extant flying squirrels, or may have been retained from some earlier shared ancestor.…”
Section: Protosciurus Mengimentioning
confidence: 99%
“…Gliding is expressed structurally in dermopterans by (i) elongate intermediate phalanges and metacarpals that support an interdigital patagium; (ii) a suite of adaptations for gliding that are convergently shared with nondermopteran gliders (e.g., Glaucomys) (24); and (iii) adaptations for quadrupedal suspension. New specimens reveal that paromomyids lack all of these features, and micromomyid plesiadapiforms lack all mitten-gliding traits and many critical gliding and suspensory features (25) (see SI Text, Part 2, and its referenced figures and tables).…”
Section: Plesiadapiform Skeletonsmentioning
confidence: 99%